Composition

By introducing silane crosslinked polymers, epoxy resins, silicone compounds and high filler rates into the two-component thermal conductivity structural glue, the problems of low mechanical properties and low thermal conductivity caused by the lack of colloidal components in the prior art are solved, and the effects of strong adhesion, rapid curing, low temperature curing and high thermal conductivity are achieved.

JP2025510062APending Publication Date: 2025-04-14WACKER CHEMIE AG
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024556296
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-21
Publication Date
2025-04-14

AI Technical Summary

Technical Problem

The two-component thermal conductivity structural glue in the prior art has shortcomings in both mechanical properties and thermal conductivity, and does not contain silica gel components, resulting in low mechanical properties and low thermal conductivity in use.

Method used

Combination components are employed, including silane crosslinking polymers, epoxy resins, epoxy resin catalysts, organosilicon compounds that do not contain nitrogen atoms directly attached to ketone groups, thermal fillers and silicone gels. The weight ratio of the silica gel to the silane crosslinked polymer of the composition is 0.5 or more, and the filling rate of the thermal conductivity filler reaches 0.80 or more to improve its thermal conductivity and mechanical properties.

Benefits of technology

It achieves excellent operating performance under low viscosity state, has strong adhesion, fast curing speed, low curing temperature and high thermal conductivity, and is suitable for a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510062000001
    Figure 2025510062000001
  • Figure 2025510062000002
    Figure 2025510062000002
  • Figure 2025510062000003
    Figure 2025510062000003
Patent Text Reader

Abstract

The present invention relates to a composition having excellent durability and adhesive strength after curing. The composition contains component (A) a silane crosslinked polymer, component (B1) an epoxy resin, component (B2) an epoxy resin curing agent, component (C) an optional organosilicon compound that does not have a nitrogen atom directly bonded to a carbonyl group, component (D) a filler, and component (E) a silicone resin.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of adhesion, in particular the use of thermally conductive adhesives. [Background technology]

[0002] China Patent Publication No. 109337630 discloses a two-component thermally conductive structural adhesive, which comprises a silane-modified polyether, an epoxy resin, a plasticizer, a thermally conductive filler, and a flame-retardant filler. The composition does not contain a silicone resin component and has poor mechanical properties.

[0003] CN104293273 discloses an adhesive comprising silane-modified polyether, epoxy resin, calcium carbonate and other fillers. The thermal conductivity of this product is low. This composition does not contain silicone resin components and has poor mechanical properties.

[0004] China Patent No. 104583277 discloses a bonding agent containing ingredients such as silane-modified polyether, silicone resin and filler. The adhesive properties of this product are not very good. Summary of the Invention

[0005] Description of the invention The present invention discloses a composition having excellent properties of strong adhesion, fast curing speed, low curing temperature and high thermal conductivity with low viscosity and excellent handling performance before curing.

[0006] The present invention relates to Component (A) a silane crosslinked polymer, Component (B1) epoxy resin, Component (B2) epoxy resin hardener, Optional component (C) an organosilicon compound that does not have a nitrogen atom directly bonded to a carbonyl group; Component (D) filler, Component (E) Silicone resin Contains The weight ratio of component (E) silicone resin to component (A) silane crosslinked polymer is 0.5 or more, preferably 0.55 to 5, more preferably 0.6 to 4, for example, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.4, 1.6, 1.8, 2.0, 2.5, 3.0, or 3.5.

[0007] The above composition, wherein the filling rate of the thermally conductive filler is 0.80 or more, preferably 0.82 or more, preferably 0.84 or more.

[0008] In the present invention, the loading factor is equal to the total amount of thermally conductive filler / total weight of the composition. Generally, a loading factor of 0.88 or higher is considered a high loading factor.

[0009] (B1) The epoxy resin is one or more selected from the group consisting of the following components: Bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, biphenyl type epoxy resins, naphthalene diol type epoxy resins, as well as phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, alicyclic epoxy resins, and heterocyclic epoxy resins (triglycidyl isocyanurate, diglycidyl hydantoin, and the like), modified epoxy resins obtained by modifying these epoxy resins with various materials, bromides and chlorides of these epoxy resins.

[0010] The (B1) epoxy resin is preferably selected from bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, and biphenyl type epoxy resins, and more preferably selected from bisphenol A type epoxy resins.

[0011] As the epoxy resin (B1), one of these resins may be used alone, or two or more of them may be used in combination.

[0012] The epoxy index of the epoxy resin (B1) is from 0.5 to 20 Eq / kg, preferably from 1 to 10 Eq / kg, and more preferably from 3 to 8 Eq / kg.

[0013] The viscosity of the epoxy resin (B1) is 5,000 to 40,000 mPa.s, preferably 5,000 to 30,000 mPa.s, and more preferably 10,000 to 20,000 mPa.s.

[0014] (B2) The epoxy resin hardener is a compound containing an active group capable of reacting with an epoxy group.

[0015] (B2) The epoxy resin curing agent is preferably a compound containing an amino group, an acid anhydride group and a hydroxyphenyl group.

[0016] (B2) The epoxy resin hardener is one or more of the following components: Dicyandiamide and its derivatives, organic acid hydrazides, aminimides, aliphatic amines, aromatic amines, tertiary amines, salts of polyamines, microcapsule type hardeners, imidazole type hardeners, acid anhydrides, and phenol novolaks.

[0017] (B2) The epoxy resin curing agent is preferably selected from an aliphatic amine, an aromatic amine, a tertiary amine, and an imidazole type curing agent, and more preferably selected from dimethylaminocresol, benzyldimethylamine, 2-ethyl-4-methylimidazole, 2-methylimidazole, 2,4,6 tris(dimethylaminomethyl)phenol DMP-30, and DMP-20.

[0018] As the epoxy resin curing agent (B2), one of these agents may be used alone, or two or more of them may be used in combination.

[0019] Additionally, various curing accelerators (B3) can be used in combination with the above-mentioned (B2) epoxy resin curing agents.

[0020] The curing accelerator (B3) is one or more selected from the group consisting of the following components: Tertiary amine-based accelerators, urea derivative-based accelerators, imidazole-based accelerators, and 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU)-based accelerators, organophosphorus-based accelerators (e.g., phosphine-based accelerators and the like), onium salt-based accelerators (e.g., phosphonium salt-based accelerators, sulfonium salt-based accelerators, ammonium salt-based accelerators, and the like), metal chelate-based accelerators, acid and metal salt-based accelerators.

[0021] The curing accelerator (B3) is preferably one or more selected from tertiary amine curing accelerators, urea derivative curing accelerators, imidazole curing accelerators, and 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU)-based curing accelerators, more preferably one or more selected from tertiary amine curing accelerators.

[0022] As the curing accelerator (B3), one of these agents may be used alone, or two or more of them may be used in combination.

[0023] The composition as described above, wherein the component (D) thermally conductive filler is selected from inorganic compounds having an average particle size D50 of less than 120 μm and a thermal conductivity of 1 W / m·K or more.

[0024] The thermal conductivity of the inorganic compound having thermal conductivity is preferably 10 W / m·K or more, and more preferably 30 W / m·K or more. Furthermore, as the inorganic compound having electrical insulation, an inorganic compound having a volume resistivity of 10 Ω·cm or more at room temperature (25°C) can be used. The volume resistivity of the inorganic compound having electrical insulation is preferably 10 5 Ω·cm or more, preferably 10 8 Ω·cm or more, particularly preferably 10 13 Note that the resistance must be Ω·cm or higher.

[0025] As inorganic compounds having both thermal conductivity and electrical insulation properties, mention may be made, for example, of borides, carbides, nitrides, oxides, silicides, hydroxides and the like. In particular, mention may be made, for example, of magnesium oxide (MgO), aluminum oxide (Al2O3), boron nitride (BN), aluminum nitride (AlN), aluminum hydroxide (Al(OH)3) and the like. Furthermore, mention may be made of silicon dioxide (SiO2), magnesium hydroxide (Mg(OH)2), titanium oxide (TiO2), zinc oxide (ZnO) and the like.

[0026] The composition as described above, wherein component (D) is 5 to 20% by weight of (D-1) a thermally conductive filler having an average particle size of 0.1 μm or more and 4 μm or less, preferably aluminum hydroxide and / or aluminum oxide; Here, for example, the average particle size of (D-1) is 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, and 2.8 μm, and the content is 8% by weight, 10% by weight, 12% by weight, 14% by weight, 16% by weight, and 18% by weight, 18 to 37% by weight of (D-2) a thermally conductive filler having an average particle size of 4 μm or more and 20 μm or less, preferably aluminum hydroxide and / or aluminum oxide; Here, for example, the average particle size of (D-2) is 6, 8, 10, 12, 14, 16, and 18 μm, and the content is 20 weight%, 22 weight%, 24 weight%, 26 weight%, 28 weight%, 30 weight%, 32 weight%, 34 weight%, and 36 weight%, 48 to 65% by weight of (D-3) a thermally conductive filler having an average particle size of 35 μm or more and 60 μm or less, preferably aluminum hydroxide and / or aluminum oxide Here, for example, the average particle size of (D-3) is 82, 84, 86, 88, 90, 92, 94, 96, and 98 μm, and the content is 50% by weight, 52% by weight, 54% by weight, 56% by weight, 58% by weight, 60% by weight, 62% by weight, and 64% by weight, comprising (D) The composition calculated assuming component (D) is 100% by weight.

[0027] The above composition, wherein the total amount of all alumina is greater than 50% by weight, preferably greater than 85% by weight, and more preferably greater than 88% by weight, calculated based on the amount of all thermally conductive fillers, component (D), being 100% by weight.

[0028] 10. The composition as described above, wherein the total amount of all alumina is greater than 50% by weight, preferably greater than 85% by weight, more preferably greater than 88% by weight, calculated based on the amount of all fillers being 100% by weight.

[0029] The above-mentioned composition, wherein the amount of spherical alumina is 85% by weight or more, preferably 90% by weight or more, calculated based on the amount of all the thermally conductive fillers of component (D) being 100% by weight.

[0030] The composition as described above, wherein the thermal conductivity of the composition is 2.0 W / m·K or more, preferably 2.2 W / m·K or more, preferably 2.3 W / m·K or more, preferably 2.4 W / m·K or more, more preferably 2.5 W / m·K or more.

[0031] In the above compositions, the aluminum hydroxide present in (D-1), (D-2) and (D-3) is all in amorphous form.

[0032] In the above compositions, the alumina present in (D-1), (D-2) and (D-3) is all of spherical morphology.

[0033] In the above composition, the amount of amorphous filler is less than 20% by weight, preferably less than 15% by weight, more preferably less than 10% by weight, calculated based on the weight of component (D) as 100% by weight.

[0034] The composition as described above, wherein at least one of the aluminum hydroxides present in (D-1), (D-2) and (D-3) has been surface-treated, preferably with component (T-1).

[0035] The composition as described above, wherein component (D) is 5 to 20% by weight of (D-1) aluminum hydroxide having an average particle size of 0.5 μm or more and 3 μm or less; 18 to 35% by weight of (D-2) alumina having an average particle size of 4 μm or more and 10 μm or more; Contains 50 to 65% by weight of (D-3) alumina having an average particle size of 35 μm or more and 50 μm or more; (D-1), (D-2) and (D-3) are calculated based on component (D) as 100% by weight of the composition.

[0036] The composition as above, wherein the weight ratio of the surface-treated thermally conductive filler to the non-surface-treated thermally conductive filler is less than 0.3, preferably less than 0.2, more preferably less than 0.15.

[0037] The above composition, wherein the weight ratio of (D-1) / (D-3) is 0.2 to 0.4, preferably 0.22 to 0.38, for example, 0.25, 0.27, 0.29, 0.31, 0.33, or 0.35.

[0038] The above-mentioned composition, wherein the weight ratio of (D-2) / (D-3) is 0.2 to 0.8, preferably 0.25 to 0.75, and preferably 0.3, 0.4, 0.5, 0.6, or 0.7.

[0039] The composition, wherein the average particle size ratio (D-2) / (D-1) is 4.0 to 12.0, for example, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, or 8.0.

[0040] The composition, wherein the average particle size ratio (D-3) / (D-1) is 30 to 100, for example, 32, 35, 40, 45, 50, 55, or 60.

[0041] The composition, wherein the average particle size ratio (D-3) / (D-2) is 7.0 to 12.0, preferably 7.5 to 10, more preferably 8.0 to 9.9, for example, 8.2, 8.4, 8.6, 8.8, 9.0, 9.2, 9.4, 9.6, or 9.8.

[0042] The definition of the average particle size refers to the integrated value of the average particle size (D50 median diameter) measured on a volume basis using a particle size measuring device LS 13 320 manufactured by BECKMAN COULTER.

[0043] (D-1) A thermally conductive filler sample is prepared by the solution method. 0.1 g of (C-1) sample is placed in 10 ml of anhydrous ethanol, dispersed by ultrasonic (100 w) so that the aluminum hydroxide is completely dispersed, and stirred for 2 minutes. Two to three drops of the sample solution are taken and placed in the sample cell of the particle size measuring device.

[0044] The thermally conductive filler samples (D-2) and (D-3) (or other thermally conductive fillers with an average particle size of 3 μm or more) were prepared by the dry powder method, and an appropriate amount of the sample dried at room temperature was placed in the filling cylinder of the particle size measuring device. The filling cylinder was inserted into the detection slot of the device.

[0045] In the present invention, the particle size distribution of the thermally conductive fillers (D-1), (D-2) and (D-3) is unimodal, or the particle size of those fillers is unimodal or almost unimodal.

[0046] In the present invention, an almost unimodal particle size distribution means that in the volume integral map of the measured sample, there may be two or more peaks, but the volume integral area of ​​the main peak accounts for more than 80%, preferably more than 85%, more preferably more than 90%, more preferably more than 95% of the total volume integral area.

[0047] Spherical fillers are filler materials that are generally spherical in external shape and are derived from amorphous fillers that have been treated by chemical and / or physical (including heat treatment) processes.

[0048] Spherical alumina is a product obtained after heat treatment of amorphous alumina, and its outer shape is usually spherical.

[0049] The optional component (D), the thermally conductive filler used in the present invention, has a moisture content of less than 1% by weight, preferably less than 0.5% by weight.

[0050] Preferably, the thermally conductive silicone composition further contains 1 to 100 parts by weight, preferably 1 to 50 parts by weight, and more preferably 1 to 10 parts by weight, of component (T-1) per 100 parts by weight of component (A). (T-1) An alkoxysilane compound represented by the following formula (1): R 1 a R 2 b Si(OR 3 ) 4-a-b (1) In the formula, each R 1 each R independently represents an alkyl group having 1 to 24 carbon atoms, preferably 6 to 24 carbon atoms, and more preferably 12 to 18 carbon atoms; 2 each independently represents an unsubstituted or substituted hydrocarbon group having 1 to 10 carbon atoms, preferably methyl or ethyl; 3 each independently represents an alkyl group having 1 to 6 carbon atoms, preferably methyl or ethyl; a represents an integer of 1 to 3, and b represents an integer of 0 to 2, provided that a+b is an integer of 1 to 3.

[0051] In the present invention, the weight ratio of the component (D) to the component (T-1) is 100-800, preferably 200-500, and more preferably 200-400.

[0052] Composition (M) as described above, wherein the viscosity of the composition is less than or equal to 2,000,000 mPa.s, preferably less than or equal to 1,000,000 mPa.s, more preferably less than or equal to 800,000 mPa.s, more preferably less than or equal to 500,000 mPa.s at 25°C according to DIN 53019, and the dynamic and static viscosities of the composition of the invention were obtained using an Anton Paar MCR302 apparatus, composition (M).

[0053] The viscosity of composition (M), if composition (M) is a two-component composition, is measured immediately after mixing.

[0054] The above-mentioned composition (M), wherein the amount of the component (A) silane crosslinked polymer is 1 to 20% by weight, preferably 1 to 15% by weight, preferably 1 to 10% by weight, more preferably 2 to 8% by weight, more preferably 3 to 7% by weight, and more preferably 3 to 5% by weight, based on the total amount of the composition (M) being calculated as 100% by weight.

[0055] The above-mentioned composition (M), wherein the sum of the component (A) silane crosslinked polymer and the component (E) silicone resin is more than 5% by weight, preferably 5 to 20% by weight, more preferably 5 to 15% by weight, more preferably 5 to 10% by weight, for example, 6, 7, 8, 9% by weight, based on the total amount of the composition (M) being calculated as 100% by weight.

[0056] The above-mentioned composition (M), wherein the amount of the component (B1) epoxy resin is 1 to 20% by weight, preferably 1 to 10% by weight, preferably 2 to 8% by weight, more preferably 3 to 7% by weight, and more preferably 4 to 7% by weight, based on the total amount of the composition (M) being calculated as 100% by weight.

[0057] The above-mentioned composition (M), wherein the total of the component (B1) epoxy resin and the component (B2) epoxy resin curing agent is 5% by weight, 5 to 20% by weight, more preferably 5 to 15% by weight, more preferably 5 to 10% by weight, for example, 6, 7, 8, or 9% by weight, based on the total amount of the composition (M) being calculated as 100% by weight.

[0058] The above-mentioned composition (M), wherein the weight ratio of the component (B1) epoxy resin to the component (B2) epoxy resin curing agent is 2 to 50, preferably 5 to 40, more preferably 10 to 35, for example, 13, 15, 17, 19, 21, 23, 25, 27, 29, 31, or 33.

[0059] In the present invention, those skilled in the art can refer to the relevant chapters of "Epoxy Resin Application Principle and Technology, Sun Manling, Machinery Industry Press, 2002" to adjust the application amount between component (B1) epoxy resin and component (B2) epoxy resin curing agent.

[0060] The above-mentioned composition (M), wherein the total of the component (A) silane crosslinked polymer, the component (E) silicone resin, the component (B1) epoxy resin and the component (B2) epoxy resin curing agent is more than 5% by weight, preferably 5 to 30% by weight, more preferably 5 to 20% by weight, and more preferably 10 to 20% by weight, based on the total amount of the composition (M) being calculated as 100% by weight.

[0061] The above composition (M), wherein the total of the component (A) silane crosslinked polymer, the component (E) silicone resin, the component (B1) epoxy resin, the component (B2) epoxy resin curing agent and the thermally conductive filler is 80% by weight, preferably 80 to 99% by weight, more preferably 90 to 98% by weight, and more preferably 93 to 98% by weight, based on the total amount of the composition (M) being calculated as 100% by weight.

[0062] The above-mentioned composition (M) is 1 to 20% by weight of component (A) a silane crosslinked polymer; 1 to 20% by weight of component (B1) an epoxy resin; 0.1 to 1 weight percent of component (B2) an epoxy resin hardener; Optional component (C) an organosilicon compound that does not have a nitrogen atom directly bonded to a carbonyl group; 75 to 85 weight percent of component (D) thermally conductive filler; 1 to 10% by weight of component (E) silicone resin Contains The total amount of all components (M) is calculated as 100% by weight.

[0063] The above-mentioned composition (M) is 3 to 15 weight percent of component (A) a silane crosslinked polymer; 3 to 10% by weight of component (B1) epoxy resin; 0.1 to 1 weight percent of component (B2) an epoxy resin hardener; Optional component (C) an organosilicon compound that does not have a nitrogen atom directly bonded to a carbonyl group; 75 to 85 weight percent of component (D) thermally conductive filler; 3 to 10% by weight of component (E) silicone resin Contains The total amount of all components (M) is calculated as 100% by weight.

[0064] The above-mentioned composition (M) is 3 to 10% by weight of component (A) a silane crosslinked polymer; 3 to 10% by weight of component (B1) epoxy resin; 0.1 to 0.5 weight percent of component (B2) an epoxy resin hardener; 0.1 to 1 weight percent of component (C) an organosilicon compound having no nitrogen atom directly bonded to a carbonyl group; 75 to 85 weight percent of component (D) thermally conductive filler; 3 to 10% by weight of component (E) silicone resin Contains The total amount of all components (M) is calculated as 100% by weight.

[0065] The composition (M) as described above, which is a two-component composition, and wherein (B1) the epoxy resin and component (B2) the epoxy resin hardener are not in the same packaging container.

[0066] Composition (M) as described above, which is a two-component composition, wherein component (A) the silane cross-linked polymer and the water are not in the same packaging container.

[0067] The above composition (M) is a two-component composition, Ingredient (M1) 3 to 10% by weight of component (A) a silane crosslinked polymer; 0.1 to 0.5 weight percent of component (B2) an epoxy resin hardener; 0.1 to 1 weight percent of component (C) an organosilicon compound having no nitrogen atom directly bonded to a carbonyl group; 32.5 to 42.5 weight percent of component (D) thermally conductive filler; Contains 3 to 10% by weight of component (E) silicone resin; Component (M2) 3 to 10% by weight of component (B1) epoxy resin; 32.5 to 42.5 weight percent of component (D) thermally conductive filler; 0.1 to 0.5% by weight water comprising The total amount of all compositions (M) is calculated as 100% by weight, composition (M).

[0068] The above-mentioned composition (M), which has an initial adhesive strength of 1Mpa or more after 24 hours and a final adhesive strength of 6Mpa or more after 14 days, after curing at room temperature with a humidity of 50%, in accordance with GB / T7124-2008.

[0069] The composition (M) as described above, comprising component (A) a silane crosslinked polymer of formula (I-1), (HO) x -Y-[O-CO-NH-(CR 1 2) b1 -SiR a (OR 2 ) 3-a ] 2-x (I-1) During the ceremony Y is a divalent polymeric group; R, which may be the same or different, are monovalent, optionally substituted hydrocarbyl groups; R 1 are the same or different and are hydrogen atoms or monovalent, optionally substituted hydrocarbyl groups; R 2 are the same or different and are hydrogen atoms or monovalent, optionally substituted hydrocarbyl groups; x is 0 or 1, a may be the same or different and is 0, 1 or 2, preferably 0 or 1, more preferably 1; b1 is 1 or 3, preferably 1; With the proviso that component (A) contains less than 15 mol %, preferably less than 10 mol %, more preferably less than 5 mol % of the polymer of formula (I-1) where x=1.

[0070] In formula (I-1), examples of R groups are each independently an alkyl group such as methyl, ethyl, n-propyl, isopropyl, 1-n-butyl, 2-n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, or tert-pentyl; a hexyl group such as n-hexyl; a heptyl group such as n-heptyl; an octyl group such as n-octyl, isooctyl, or 2,2,4-trimethylpentyl; a nonyl group such as n-nonyl; a decyl group such as n-decyl; and a n-dodecyl group. cycloalkyl groups such as cyclopentyl, cyclohexyl, cycloheptyl and methylcyclohexyl groups; alkenyl groups such as vinyl, 1-propenyl and 2-propenyl groups; aryl groups such as phenyl, naphthyl, anthryl and phenanthryl groups; alkaryl groups such as o-, m- and p-tolyl groups; aralkyl groups such as xylyl and ethylphenyl groups, benzyl and α- and β-phenylethyl groups.

[0071] In formula (I-1), examples of substituted R groups are independently haloalkyl groups such as 3,3,3-trifluoro-n-propyl, 2,2,2,2',2',2'-hexafluoroisopropyl and heptafluoroisopropyl groups, and haloaryl groups such as o-, m- and p-chlorophenyl groups.

[0072] Preferably, the R groups are each independently a monovalent hydrocarbyl group optionally substituted with halogen atoms and having 1 to 6 carbon atoms, more preferably an alkyl group having 1 or 2 carbon atoms, especially a methyl group.

[0073] In formula (I-1), R 1 Examples of groups are, each independently, a hydrogen atom or a group defined for R.

[0074] Preferably, R 1 The groups are each independently a hydrogen atom or a hydrocarbyl group having 1 to 20 carbon atoms, in particular a hydrogen atom.

[0075] In formula (I-1), R 2 Examples of radicals are independently a hydrogen atom or the examples given for the R radicals.

[0076] Preferably, R 2 The groups are each independently an alkyl group optionally substituted with hydrogen or halogen atoms and having 1 to 10 carbon atoms, more preferably having 1 to 4 carbon atoms, especially a methyl or ethyl group.

[0077] In formula (I-1), examples of the polymeric group Y are independently polyester, polyether, polyurethane, polyalkylene, and polyacrylic acid groups.

[0078] The polymeric groups Y are preferably, each independently, an organic polymer containing as a polymer chain a polyoxyalkylene such as polyoxyethylene, polyoxypropylene, polyoxybutylene, polyoxytetramethylene, polyoxyethylene-polyoxypropylene copolymers and polyoxypropylene-polyoxybutylene copolymers, a hydrocarbon polymer such as polyisobutylene and copolymers of polyisobutylene and isoprene, polychloroprene, polyisoprene, polyurethanes, polyesters, polyamides, polyacrylic acid, polymethacrylic acid, vinyl polymers and / or polycarbonates.

[0079] More preferably, each Y group is a polyoxyalkylene group, more preferably a linear polyoxyalkylene group.

[0080] The polymers of formula (I-1) used according to the invention preferably have the formula HO-Y-OH(V) The polymer of formula OCN-(CR 1 2) b1 -SiR a (OR 2 ) 3-a (VI-1) with a silane of All groups and indices have one of the definitions according to formula (I-1). Of great importance is that the reaction achieves substantially complete termination of the existing chain ends.

[0081] Polymer systems in which nearly all of the OH functionality is substantially completely terminated with the isocyanate-functional silane of formula (VI-1) have better curability.

[0082] Suitable corresponding preparation processes for component (A) and also examples of component (A) itself are described, inter alia, in EP 1 535 940 (paragraphs

[0005] to

[0025] and Examples 1 to 3 and Comparative Examples 1 to 4) or EP 1 896 523 (paragraphs

[0008] to

[0047] ), which form part of the disclosure of the present application.

[0083] The compounds (A) used according to the present invention may be prepared separately and without mixing with each other until the composition (M) of the present invention is obtained. However, the compounds (A) can also be prepared together by reacting together a mixture of polyols of formula (V) with an isocyanate-functional silane of formula (VI-1).

[0084] Average molecular weight M of compound (A) n is at least 5,000 g / mol, preferably at least 10,000 g / mol, more preferably at least 11,000 g / mol, and preferably at most 30,000 g / mol, more preferably at most 24,000 g / mol and in particular at most 22,000 g / mol.

[0085] Number average molar mass M n was determined by size exclusion chromatography (SEC) against polystyrene standards in THF at 60°C with a flow rate of 1.2 ml / min and by RI detection (differential refractive index detector) on a Styragel HR3-HR4-HR5-HR5 column set from Waters Corp. USA with an injection volume of 100 μl.

[0086] The viscosity of component (A) is preferably at least 0.2 Pas, more preferably at least 1 Pas, and most preferably at least 5 Pas, and preferably at most 700 Pas, more preferably at most 100 Pas.

[0087] Component (A) used according to the invention may contain only one type of compound of formula (I-1) or different types of compounds of formula (I-1). for example, The silane end groups in component (A1) are b1=1, R 1 =H and a=1, The silane end groups in component (A2) are b1=3, R 1 =H and a=0.

[0088] In a particular embodiment, the composition (M) of the present invention comprises a polymer (A1) (wherein b1=1, R 1 =H and a=1) and component (E) a silicone resin.

[0089] In a particular embodiment, the composition (M) of the present invention comprises a polymer (A2) (wherein b1=3, R 1 =H and a=0) and component (E) a silicone resin.

[0090] In a further particular embodiment, composition (M) of the invention simultaneously contains polymer (A1) and polymer (A2).

[0091] In addition to components (A1) / (A2) and (E) the silicone resin, the composition (M) of the present invention may further comprise substances such as (C) an organosilicon compound having no nitrogen atom bonded directly to a carbonyl group, (H) a water scavenger, and (J) additives.

[0092] The organosilicon compound (C) optionally present in the composition (M) of the invention and which does not have a nitrogen atom directly bonded to a carbonyl group preferably has the formula D e Si(OR 7 ) f R 8 g O (4-e-f-g) / 2 (III) is an organosilicon compound containing units of R 7 are the same or different and are hydrogen atoms or optionally substituted hydrocarbyl groups; D is a monovalent, SiC-bonded group, which may be the same or different, having no nitrogen atom directly bonded to a carbonyl group; R 8are the same or different, monovalent, optionally substituted, SiC-bonded, nitrogen-free organic radicals; e is 0, 1, 2, 3 or 4, preferably 1; f is 0, 1, 2 or 3, preferably 1, 2 or 3, more preferably 2 or 3; g is 0, 1, 2 or 3, preferably 1 or 0; provided that the sum of e+f+g is 4 or less and there is at least one D group per molecule.

[0093] The organosilicon compound (C) used according to the invention may be either a silane (i.e. a compound with e+f+g=4) or a siloxane (i.e. a compound containing units with e+f+g≦3), preferably a silane.

[0094] an optionally substituted hydrocarbyl group R 7 Examples of are those shown for the R group.

[0095] R 7 The radical is preferably a hydrocarbyl radical optionally substituted by hydrogen or halogen atoms and having 1 to 18 carbon atoms, more preferably a hydrogen atom or a hydrocarbyl radical having 1 to 10 carbon atoms, in particular a methyl or ethyl radical.

[0096] R 8 Examples of radicals are those given for R.

[0097] R 8 The radicals preferably comprise hydrocarbyl groups optionally substituted with halogen atoms and having from 1 to 18 carbon atoms, more preferably hydrocarbyl groups having from 1 to 5 carbon atoms, especially methyl groups.

[0098] The D group is preferably H2N(CH2)3-, H2N(CH2)2NH(CH2)3-, H2N(CH2)2NH(CH2)2NH(CH2)3-, H3CNH(CH2)3-, C2H5NH(CH2)3-, C3H7NH(CH2)3-, C4H9NH(CH2)3-, C5H 11 NH(CH2)3-, C6H 13 NH(CH2)3-, C7H 15 NH(CH2)3-, H2N(CH2)4-, H2N-CH2-CH(CH3)-CH2-, H2N(CH2)5-, cyclo-C5H9NH(CH2)3-, cyclo-C6H 11 NH(CH2)3-, phenyl-NH(CH2)3-, (CH3)2N(CH2)3-, (C2H 15 )2N(CH2)3-, (C3H7)2N(CH2)3-, (C4H9)2N(CH2)3, (C5H 11 )2N(CH2)3, (C6H 13 )2N(CH2)3, (C7H 15 )2N(CH2)3-, H2N(CH2)-, H2N(CH2)2NH(CH2)-, H2N(CH2)2NH(CH2)2NH(CH2)-, H3CNH(CH2)-, C2H5NH(CH2)-, C3H7NH(CH2)-, C4H9NH(CH2)-, C5H 11 NH(CH2)-, C6H 13 NH(CH2)-, C7H 15 NH(CH2)-, cyclo-C5H9NH(CH2)-, cyclo-C6H 11 NH(CH2)-, phenyl-NH(CH2)-, (CH3)2N(CH2)-, (C2H5)2N(CH2)-, (C3H7)2N(CH2)-, (C4H9)2N(CH2)-, (C5H 11 )2N(CH2)-, (C6H 13 )2N(CH2)-, (C7H 15)2N(CH2)-, (CH3O)3Si(CH2)3NH(CH2)3-, (C2H5O)3Si(CH2)3NH(CH2)3-, (CH3O)2(CH3)Si(CH2)3NH(CH2)3- and (C2H5O)2(CH3)Si(CH2)3NH(CH2)3- as well as reaction products of the above-mentioned primary amino acids with compounds having an epoxy group or a double bond which reacts with the primary amino acids. The D group is preferably H2N(CH2)3-, H2N(CH2)2NH(CH2)3- or cyclo-CH 11 It is the NH(CH2)3- group.

[0099] The silanes of formula (III) used according to the invention are preferably H2N(CH2)3-Si(OCH3)3, H2N(CH2)3-Si(OC2H5)3, H2N(CH2)3-Si(OCH3)2CH3, H2N(CH2)3-Si(OC2H5)2CH3, H2N(CH2)2NH(CH2)3-Si(OCH3)3, H2N(CH2)2NH(C H2)3-Si(OC2H5)3, H2N(CH2)2NH(CH2)3-Si(OCH3)2CH3, H2N(CH2)2NH(CH2)3-Si(OC2H5)2CH3, H2N(CH2)2NH(CH2)2NH(CH2)3-Si(OCH3)3, H2N(CH2)2NH(CH2)2NH(CH2)3-Si(OC2H5)3, Cyclo-C6H 11 NH(CH2)3-Si(OCH3)3, cyclo-CH 11 NH(CH2)3-Si(OC2H5)3, cyclo-CH 11 NH(CH2)3-Si(OCH3)2CH3, cyclo-CH 11 NH(CH2)3-Si(OC2H5)2CH3, phenyl-NH(CH2)3-Si(OCH3)3, phenyl-NH(CH2)3-Si(OC2H5)3, phenyl-NH(CH2)3-Si(OCH3)2CH3, phenyl-NH(CH2)3-Si(OC2H5)2CH3, HN((CH2)3-Si(OCH3)3)2, HN((CH2)3-Si(OC2H)3)2HN((CH2)3-Si(OCH3)2CH3)2, HN((CH2)3-Si(OC2H5)2CH3)2, cyclo-C6H 11NH(CH2)-Si(OCH3)3, cyclo-CH 11 NH(CH2)-Si(OC2H5)3, cyclo-CH 11 NH(CH2)-Si(OCH3)2CH3, cyclo-CH 11 NH(CH2)-Si(OC2H5)2CH3, phenyl-NH(CH2)-Si(OCH3)3, phenyl-NH(CH2)-Si(OC2H5)3, phenyl-NH(CH2)-Si(OCH3)2CH3, phenyl-NH(CH2)-Si(OC2H5)2CH3, phenyl-NH(CH2)-Si(OC2H5)2CH3, and also partial hydrolysates thereof, H2N(CH2)3-Si(OCH3)3 , H2N(CH2)3-Si(OC2H5)3, H2N(CH2)3-Si(OCH3)2CH3, H2N(CH2)3-Si(OC2H)2CH3, H2N(CH2)2NH(C H2)3-Si(OCH3)3, H2N(CH2)2NH(CH2)3-Si(OC2H5)3, H2N(CH2)2NH(CH2)3-Si(OCH3)2CH3, Cyclo-C6H 11 NH(CH2)3-Si(OCH3)3, cyclo-CH 11 NH(CH2)3-Si(OC2H5)3 and cyclo-CH 11 Preference is given to NH(CH2)3-Si(OCH3)2CH3 and their respective partial hydrolysates, followed by H2N(CH2)3-Si(OCH3)3, H2N(CH2)3-Si(OC2H5)3, H2N(CH2)3-Si(OCH3)2CH3, H2N(CH2)3-Si(OC2H5)2CH3, H2N(CH2)2NH(CH2)3-Si(OCH3)3, H2N(CH2)2NH(CH2)3-Si(OCH3)2CH3, cyclo-C6H 11 NH(CH2)3-Si(OCH3)3, cyclo-CH 11 Particular preference is given to NH(CH2)3-Si(OCH3)2CH3 and the respective partial hydrolysates.

[0100] The organosilicon compound (C) optionally used according to the invention may also assume the function of curing catalyst or cocatalyst in the composition (M) of the invention.

[0101] Furthermore, the organosilicon compound (C) optionally used according to the present invention may function as an adhesion promoter and / or as a water scavenger.

[0102] The organosilicon compounds (C) optionally used in accordance with the present invention are either commercially available or can be prepared by standard chemical methods.

[0103] When the composition (M) of the present invention contains component (C), the amount thereof is preferably 0.01 to 25 parts by weight, more preferably 2 to 20 parts by weight, in particular 5 to 18 parts by weight, in particular 10 to 16 parts by weight, based in each case on 100 parts by weight of component (A). The composition (M) of the present invention preferably contains component (C).

[0104] The composition (M) used in the present invention may also contain (Q1) and / or (Q2) non-thermally conductive fillers. (Q1) Non-reinforcing fillers, i.e. preferably up to 50 m 2 fillers having a BET surface area of ​​0.1 g / g, such as diatomaceous earth, calcium silicate, zirconium silicate, talc, kaolin, zeolites, barium sulfate, precipitated and / or ground chalk which may be either coated or uncoated, gypsum, silicon nitride, silicon carbide, boron nitride, glass and polymer powders such as polyacrylonitrile powders; (Q2) Reinforcing filler, i.e., 50m 2Fillers with a BET surface area of ​​more than 1000 nm / g, for example fumed silica, precipitated silica, precipitated chalk, carbon blacks such as furnace black and acetylene black, and mixtures of silicon-aluminium oxides with high BET surface areas, fillers in the form of hollow spheres, for example ceramic microbeads such as those available under the trade name Zeeospheres™ from 3M Deutschland GmbH (Neuss, Germany), elastic polymer beads or glass beads such as those available under the trade name EXPANCEL® from AKZO NOBEL, Expancel (Sundsvall, Sweden), fibrous fillers such as asbestos and polymer fibers. The mentioned fillers may be hydrophobized, for example by treatment with organosilanes or organosiloxanes or with stearic acid, or by etherification of the hydroxyl groups to alkoxyl groups.

[0105] In the compositions of the present invention, the amount of component (Q1) non-reinforcing filler and component (Q2) reinforcing filler is less than 1% by weight, preferably less than 0.1% by weight, calculated based on the weight of the composition being 100% by weight.

[0106] The optional silicone resin (E) present in the composition (M) of the present invention comprises the formula (II) R 3 c (R 4 O) d SiO (4-c-d) / 2 (II) During the ceremony R 3 are the same or different and represent hydrogen atoms or optionally substituted monovalent hydrocarbon radicals bonded to SiC, R 4 may be the same or different and represent a hydrogen atom or an optionally substituted monovalent hydrocarbon radical; c is 0, 1, 2 or 3; d is 0, 1, 2 or 3; The sum of c+d is less than or equal to 3 and c is equal to 0 or 1 for at least 50%, preferably at least 85%, more preferably at least 90% of the units of formula (II).

[0107] The silicone resin (E) preferably contains at least 95% by weight of units of the formula (II). It is particularly preferred that the silicone resin (E) consists exclusively of units of the formula (II).

[0108] In formula (II), the group R 3 Examples of are those specified above for R in formula (I-1).

[0109] base R 3 preferably comprises a monovalent SiC-bonded aliphatic or aromatic hydrocarbon radical having 1 to 18 carbon atoms, optionally substituted with halogen atoms, more preferably a methyl or phenyl radical. In particular, all radicals R 3 are exclusively methyl and phenyl groups.

[0110] In formula (II), the group R 4 Examples of are a hydrogen atom or the examples specified for the R group in formula (I-1).

[0111] R 4 The group preferably comprises an alkyl group optionally substituted with hydrogen or halogen atoms and having 1 to 10 carbon atoms, more preferably a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, more preferably a methyl, ethyl, or butyl group, and most preferably a methyl group.

[0112] Phenyl silicone resins are preferably used as resin (E). Most preferably, the phenyl silicone resin (E) consists exclusively of units of formula (II), with at least 10%, preferably at least 50%, more preferably at least 60% of all units of formula (II) having at least one SiC-bonded phenyl group.

[0113] A silicone resin (E) in which c+d is less than 3 is preferably used.

[0114] In one embodiment, a phenylsilicone resin (E) is used that contains at least 50%, more preferably at least 60%, of units of formula (II) where c is 1, in each case based on the total number of units of formula (II).

[0115] In a preferred embodiment, a silicone resin (E) is used which consists exclusively of units of formula (II), where c is 0, 1 or 2, with the proviso that in at least 50% of the units of formula (II), c is equal to 0 or 1.

[0116] In a preferred embodiment, a silicone resin (E) consisting exclusively of units of formula (II) in which c is 1 or 2 is used.

[0117] In a preferred embodiment, a silicone resin (E) is used which consists exclusively of units of formula (II) in which c is 1.

[0118] Preference is given in each case to silicone resins (E) which have at least 70%, more preferably at least 80%, of units of formula (II) in which d is 0 or 1, based on the total number of units of formula (II).

[0119] Preference is given in each case to silicone resins (E) which have from 30% to 95%, more preferably from 30% to 90%, of units of formula (II) in which d is 0, based on the total number of units of formula (II).

[0120] Examples of silicone resins (E) are organopolysiloxane resins, having the formula SiO4 / 2, Si(OR 4 )O 3 / 2 , Si(OR 4 )2O 2 / 2 , and Si(OR 4 )3O 1 / 2 (Q) unit, formula PhSiO 3 / 2 , PhSi(OR 4 )O 2 / 2 , and PhSi(OR4 )2O 1 / 2 (T) unit, formula Me2SiO 2 / 2 and Me2Si(OR 4 )O 1 / 2 and similarly the (D) unit of the formula Me3SiO 1 / 2 wherein Me is a methyl group, Ph is a phenyl group, and R 4 is a methyl, ethyl or butyl group, preferably a methyl group, and the resin preferably contains 0 to 2 moles of (Q) units, 0 to 2 moles of (D) units, and 0 to 2 moles of (M) units per mole of (T) units.

[0121] Preferred examples of silicone resins (E) are organopolysiloxane resins of the formula PhSiO 3 / 2 , PhSi(OR 4 )O 2 / 2 , and PhSi(OR 4 )2O 1 / 2 T units and the formula MeSiO 3 / 2 , MeSi(OR 4 )O 2 / 2 , and MeSi(OR 4 )2O 1 / 2 and likewise optionally with the formula Me2SiO 2 / 2 and Me2Si(OR 4 )O 1 / 2 wherein Me is a methyl group, Ph is a phenyl group, and R 4 is a methyl, ethyl, or butyl group, preferably a methyl group. The molar ratio of phenyl silicone units to methyl silicone units is 0.5 to 2.0. The amount of D units in these silicone resins is preferably 10% by weight or less.

[0122] Further, a preferred example of the silicone resin (E) is represented by the formula PhSiO 3 / 2 , PhSi(OR 4 )O 2 / 2 , and PhSi(OR 4 )2O 1 / 2The total of the T units accounts for 90% by weight, preferably 95% by weight, and more preferably 99% by weight or more of all the units of the silicone resin (E), calculated based on 100% by weight of all the units of the silicone resin (E); Ph is a phenyl group; R 4 is a methyl, ethyl, or butyl group, preferably a methyl group.

[0123] The silicone resin (E) preferably has a number average molar mass M of at least 400 g / mol and more preferably at least 600 g / mol. n The average molar mass M n is preferably equal to or less than 400,000 g / mol, more preferably equal to or less than 100,000 g / mol, most preferably equal to or less than 50,000 g / mol. The silicone resin (E) may be either solid or liquid at 23° C. and 1000 hPa, with liquid silicone resins being preferred.

[0124] The silicone resin (E) may be used either in pure form or in the form of a solution in a suitable solvent.

[0125] However, it is preferred to use a silicone resin (E) which does not contain organic solvents.

[0126] The catalyst (F) used in the composition (M) of the invention may be any desired catalyst currently known for compositions which cure by silane condensation.

[0127] The metal-containing curing catalyst (F) is selected from organic titanium and tin compounds, preferably selected from the group consisting of titanic esters, tetrabutyl titanate, tetrapropyl titanate, tetraisopropyl titanate, titanium tetraacetylacetonate, dibutyltin dilaurate, dibutyltin dimaleate, dibutyltin diacetate, dibutyltin dioctanoate, dibutyltin acetylacetonate, dibutyltin oxide, and the corresponding dioctyltin compounds.

[0128] The metal-free curing catalyst (F) is selected from basic compounds, preferably from the group consisting of triethylamine, tributylamine, 1,4-diazabicyclo[2.2.2]octane, 1,5-diazabicyclo[4.3.0]non-5-ene, 1,8-diazabicyclo[5.4.0]undec-7-ene, N,N-bis(N,N-dimethyl-2-amino-ethyl)methylamine, pentamethylguanidine, tetramethylguanidine and further guanidine derivatives, N,N-dimethylcyclohexylamine, N,N-dimethylphenylamine and N-ethylmorpholine.

[0129] As catalysts (F) it is likewise possible to use acidic compounds such as phosphoric acid and its esters, toluenesulfonic acid, sulfuric acid, nitric acid, or other organic carboxylic acids such as acetic acid and benzoic acid.

[0130] If the composition (M) of the invention contains a catalyst (F), its amount is preferably at most 1 part by weight, more preferably at most 0.1 part by weight, more preferably at most 0.01 part by weight, in each case based on 100 parts by weight of component (A).Preferably, the composition (M) of the invention does not contain a catalyst (F).

[0131] When the composition (M) of the present invention comprises an adhesion promoter (G), the adhesion promoter may be any desired adhesion promoter heretofore described for systems cured by silane condensation.

[0132] Examples of adhesion promoters (G) are epoxy silanes, such as glycidoxypropyltrimethoxysilane, glycidoxypropylmethyldimethoxysilane, glycidoxypropyltriethoxysilane or glycidoxypropylmethyldiethoxysilane, 2-(3-triethoxysilylpropyl)maleic anhydride, N-(3-trimethoxysilylpropyl)urea, N-(3-triethoxysilylpropyl)urea, N-(trimethoxysilylmethyl)urea, N-(methyl-dimethoxysilylmethyl)urea, N-(3-triethoxysilylmethyl)urea, N-(3-methyldiethoxysilylmethyl)urea, O-(methylcarbamatomethyl)-methyldimethoxysilane, O-(methylcarbamatomethyl)tri ... silane, O-(ethylcarbamatomethyl)methyldiethoxysilane, O-(ethylcarbamatomethyl)-triethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, methacryloyloxymethyltrimethoxysilane, methacryloyloxymethylmethyldimethoxysilane, methacryloyloxymethyltriethoxysilane, methacryloyloxymethylmethyldiethoxysilane, 3-acryloyloxypropyltrimethoxysilane, acryloyloxymethyltrimethoxysilane, acryloyloxymethylmethyldimethoxysilane, acryloyloxymethyltriethoxysilane and acryloyloxymethylmethyldiethoxysilane, and partial condensates thereof.

[0133] If the composition (M) of the invention comprises an adhesion promoter (G), its amount is preferably at most 3 parts by weight, more preferably at most 1.5 parts by weight, in each case based on 100 parts by weight of the composition (M).

[0134] The water scavenger (H) used in the composition (M) of the present invention may be any desired water scavenger described for systems that cure by silane condensation.

[0135] Examples of water scavengers (H) are silanes, such as vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, O-(methylcarbamatomethyl)methyldimethoxysilane, O-(methylcarbamatomethyl)trimethoxysilane, O-(ethylcarbamatomethyl)methyldiethoxysilane, and also O-(ethylcarbamatomethyl)triethoxysilane, and / or their partial condensates, and also orthoesters, such as 1,1,1-trimethoxyethane, 1,1,1-triethoxyethane, trimethoxymethane and triethoxymethane.

[0136] When the composition (M) of the invention comprises a water scavenger (H), its amount is not more than 1 part by weight, more preferably not more than 0.3 parts by weight, in each case based on 100 parts by weight of the composition (M). The composition of the invention preferably does not comprise a water scavenger (H).

[0137] When the composition (M) of the present invention comprises a non-reactive plasticizer (I), the non-reactive plasticizer (I) may be any desired plasticizer known to date and typical for silane crosslinking systems.

[0138] Non-reactive plasticizers (I) are preferably selected from the group consisting of phthalates (dioctyl phthalate, diisooctyl phthalate and diundecyl phthalate), perhydrogenated phthalates (diisononyl cyclohexane 1,2-dicarboxylate and dioctyl cyclohexane 1,2-dicarboxylate), adipates (dioctyl adipate), benzoates, glycol esters, esters of saturated alkanediols (2,2,4-trimethylpentane-1,3-diol monoisobutyrate and 2,2,4-trimethylpentane-1,3-diol diisobutyrate), phosphates, sulfonates, polyesters, polyethers (preferably with a molar mass M of 400 to 10 000 g / mol). n(polyethylene glycols and polypropylene glycols having the formula (I)), polystyrene, polybutadiene, polyisobutylene, methyl dimethicone, phenyl dimethicone, trifluoromethyl dimethicone, hydroxy dimethicone, mineral oil, paraffinic hydrocarbons and high molecular weight branched hydrocarbons.

[0139] Preferably, the non-reactive plasticizer (I) is selected from the group consisting of polyoxypropylene monohydric alcohols, polyoxypropylene glycols, polyoxyethylene monohydric alcohols, polyoxyethylene glycols, polyoxypropylene-polyoxyethylene block copolymers, polyether polyols, and the above-mentioned terminal modifications.

[0140] The amount of any non-reactive plasticizer (I) in the composition (M) of the present invention is less than 1% by weight, preferably less than 0.5% by weight, more preferably less than 0.1% by weight, based on the component (A) silane crosslinked polymer calculated on 100% by weight. The composition (M) of the present invention preferably does not contain any non-reactive plasticizer (I).

[0141] The additive (J) used in the composition (M) of the present invention may be any desired typical additive useful in silane crosslinking systems.

[0142] The additives (J) used according to the invention are preferably antioxidants, UV stabilizers, such as so-called HALS compounds, fungicides and pigments.

[0143] When the composition (M) of the present invention contains an additive (J), the amount thereof is preferably 0.01 to 30 parts by weight, more preferably 0.1 to 10 parts by weight, based in each case on 100 parts by weight of component (A). The composition (M) of the present invention preferably contains an additive (J).

[0144] The admixtures (K) used according to the invention are preferably tetraalkoxysilanes, such as tetraethoxysilane, and / or partial condensates thereof, rheological additives, flame retardants and organic solvents.

[0145] Preferred reactive plasticizers (K) are compounds having 6 to 40 carbon atoms and containing an alkyl chain with a group that reacts with the compounds (A1) / (A2). Examples are isooctyltrimethoxysilane, isooctyltriethoxysilane, N-octyltrimethoxysilane, N-octyltriethoxysilane, decyltrimethoxysilane, decyltriethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, tetradecyltrimethoxysilane, tetradecyltriethoxysilane, hexadecyltrimethoxysilane and hexadecyltriethoxysilane.

[0146] The rheological additive (K) is preferably a polyamide wax, hydrogenated castor oil or stearic acid.

[0147] Examples of organic solvents (K) are low molecular weight ethers, esters, ketones, aromatic and aliphatic and optionally halogenated hydrocarbons and alcohols, preference being given to the latter.

[0148] The amount of organic solvent (K) applied is less than 1 part by weight, preferably less than 0.1 part by weight, based on 100 parts by weight of component (A). Preferably, no organic solvent (K) is added to the composition (M) of the present invention.

[0149] Composition (M) according to the invention is moisture-curable, meaning that the composition is preferably a liquid or pasty composition which hardens on contact with water and / or atmospheric humidity.

[0150] Use of the composition (M) in a curable composition.

[0151] The composition (M) of the present invention can be cured at room temperature conditions and has a suitable pot life, which is less than 10 hours, preferably less than 5 hours.

[0152] The composition (M) of the invention can be prepared by any method known per se, such as the standard methods and mixing processes for preparing moisture-curable compositions.

[0153] The present invention further provides a process for preparing the composition (M) of the present invention by mixing the separate components in any desired order.

[0154] Preferably, the catalytically active components (C) and / or (F) are not added until the end of the mixing operation.

[0155] This mixing operation may be effected at room temperature, i.e. at a temperature between 0 and 30° C., and at the pressure of the surrounding air, i.e. about 900 to 1100 hPa. If necessary, this mixing may alternatively be effected at elevated temperatures, for example at temperatures in the range of 30 to 130° C. Furthermore, it is possible to mix intermittently or constantly under reduced pressure, for example at a pressure between 30 and 500 hPa absolute, in order to remove volatile compounds and / or air.

[0156] The mixing operation of the present invention is preferably affected by the exclusion of moisture.

[0157] The process of the present invention can be carried out continuously or batchwise.

[0158] The composition (M) of the present invention is a one-component composition that can be stored with the exclusion of water and can crosslink at room temperature upon the ingress of water.

[0159] Alternatively, the composition (M) of the present invention is part of a two-component crosslinking system, where an OH-containing compound, such as water, is added to the second component.

[0160] The composition (M) of the present invention is a two-component crosslinked system, and the weight ratio of the first component to the second component is (0.1-50):1, preferably (0.5-30):1, more preferably (0.5-8):1, and more preferably (0.8-1.2):1. The first component contains the composition (M1) of the present invention, The second component contains an optional catalyst (F) and an OH compound, the OH compound including water, preferably the OH compound is water.

[0161] The composition (M) of the present invention is a two-component crosslinked system, and the viscosity of the first component is 500 to 500,000 cP, preferably 10,000 to 300,000 cP, preferably 20,000 to 200,000 cP, and more preferably 30,000 to 100,000 cP.

[0162] The viscosity of the second component is 10,000 to 1,500,000 cP, preferably 50,000 to 1,200,000 cP, and more preferably 250 to 1,000,000 cP, or 300,000 cP, 500,000 cP, 600,000 cP, 700,000 cP, or 900,000 cP.

[0163] The water content of the composition (M) of the present invention is 0.01 to 15 parts by weight, preferably 0.01 to 10 parts by weight, more preferably 0.1 to 10 parts by weight, more preferably 6 to 10 parts by weight, or 0.6, 0.8, 2, 3, 4, 5, 6, 7, 8, or 9 parts by weight, based on 100 parts by weight of the component (A).

[0164] The above composition (M) may be crosslinked to create a dual cure product.

[0165] The composition (M) of the present invention preferably cures at room temperature. The composition may also crosslink, if necessary, at temperatures higher or lower than room temperature, for example at temperatures from -5 to 15°C or 30 to 50°C.

[0166] Preference is given to carrying out the crosslinking at a pressure of 100-1100 hPa, in particular under the pressure of the surrounding air, i.e. at a pressure of about 900-1100 hPa.

[0167] The present invention further provides a method of coating and / or caulking and / or potting, in which the composition (M) according to the present invention is applied and / or caulked and / or potted into gaps between substrates and / or electronic devices before crosslinking and / or curing.

[0168] Electronic devices include cells, battery modules, battery packs, sensors, actuators, wireless power sources, photovoltaic devices, wireless transmitters, antennas, nanoelectromechanical systems, and microelectromechanical systems.

[0169] The substrates include metal substrates, polymer substrates, and inorganic material substrates, and the substrates are preferably copper, aluminum, aluminum-magnesium alloy, metal oxides, ceramics, PET film, and ceramic PCB circuit boards.

[0170] The present invention further provides a product obtainable by the above process.

[0171] Use of the composition (M) as defined above in the field of batteries, preferably in the field of power batteries, more preferably in CTP batteries (CELLtoPACK batteries), module-free batteries, blade batteries, honeycomb batteries.

[0172] In the examples set forth herein below, all viscosities are at a temperature of 25° C. Unless otherwise specified, the examples which follow are carried out at ambient air pressure, i.e., about 1000 hPa, and room temperature, i.e., about 23° C. or the temperature established upon combining with the reactants at room temperature without further heating or cooling, and a relative humidity of about 50%. Furthermore, all numbers of parts and percentages are by weight, unless otherwise specified. EXAMPLES

[0173] Embodiment Sample (A1), a silane crosslinked polymer, a polypropylene glycol having silane end-capping at both ends, an average molar mass Mn of 8000-20000 g / mol, and containing the formula -OC(=O)-NH-(CH2)-SiMe(OCH3)2 as an end group, belongs to component (A) silane crosslinked polymer; Aminopropyltrimethoxysilane belongs to the component (C) organosilicon compound that does not have a nitrogen atom directly bonded to a carbonyl group. Contains T units, methyl and phenyl, Mw 1000-2000 g / mol, viscosity 250-350 mm 2 Silicone resin 1, which is / s, belongs to component (E) silicone resin. The above materials are provided by WACKER CHEMIE AG.

[0174] Bisphenol A Epoxy Resin, Bisphenol A Diglycidyl Ether CAS1675-54-3, Epoxy Value Epoxy Index 5.42Eq / kg, Viscosity 14,661mPa.s, belongs to component (B1) epoxy resin; DMP-30, 2,4,6 tris(dimethylaminomethyl)phenol belongs to component (B2) epoxy resin hardener. (D-1) Aluminum hydroxide having an average particle size of 1.5 μm and surface-treated with component (T-1); (D-2) Spherical alumina with an average particle size of approximately 5.5 μm (D-3) Spherical alumina with an average particle size of about 40 μm The above materials are commercially available.

[0175] The thermal conductivity of the samples was tested using a TIM Testing Instrument 1300 from Analysis Tech Inc. according to ASTM D5470.

[0176] Preparation method example The ingredients listed in Table 1 were charged into a reaction vessel equipped with stirring, cooling and heating devices. At room temperature, the liquid materials were mixed uniformly, and then the powdered materials were added to the liquid materials. However, the aminopropyltrimethoxysilane and DMP-30 should be added last. The water was then removed and reserved for later use.

[0177] The raw materials and amounts used for each of the examples and comparative examples are shown in Table 1.

[0178] [Table 1]

[0179] The dynamic viscosity of components M1 and M2 in Table 1 was measured according to DIN 53019 using an Anton Paar MCR302 instrument. Components M1 and M2 were mixed and the dynamic and static viscosity of the composition of the invention was immediately tested.

[0180] The compositions were cured at room temperature and 50% humidity. The adhesive strength of the products was tested after 24 hours and 14 days of curing according to GB / T7124-2008.

[0181] [Table 2]

[0182] From Table 2, it can be seen that Comparative Example 4, which does not contain a silicone resin, has poor adhesive performance.

[0183] When using a larger amount of component (E) silicone resin, that is, when the weight ratio of component (E) silicone resin to component (A) silane crosslinked polymer is 0.95, the composition of Example 1 shows good final adhesive strength.When the weight ratio is 0.33, the adhesive performance of the composition obtained by Comparative Example 2 is significantly lower than that of the composition of Example 1.

Claims

1. Component (A) a silane crosslinked polymer, Component (B1) epoxy resin, Component (B2) epoxy resin curing agent, Optional component (C) an organosilicon compound that does not have a nitrogen atom directly bonded to a carbonyl group; Component (D) filler, Component (E) Silicone Resin A composition (M) comprising: the weight ratio of the component (E) silicone resin to the component (A) silane crosslinked polymer is 0.5 or more, preferably 0.55 to 5, and more preferably 0.6 to 4; Composition (M).

2. The composition (M) according to claim 1, wherein the filling rate of the thermally conductive filler is 0.80 or more, preferably 0.82 or more, preferably 0.84 or more.

3. Component (D) is 5 to 20% by weight of (D-1) a thermally conductive filler having an average particle size of 0.1 μm or more and 4 μm or less, preferably aluminum hydroxide and / or aluminum oxide; 18 to 37% by weight of (D-2) a thermally conductive filler having an average particle size of 4 μm or more and 20 μm or less, preferably aluminum hydroxide and / or aluminum oxide; 48 to 65% by weight of (D-3) a thermally conductive filler having an average particle size of 35 μm or more and 60 μm or less, preferably aluminum hydroxide and / or aluminum oxide comprising In (D-1), (D-2) and (D-3), the component (D) in the composition is calculated as 100% by weight. The composition (M) according to claim 1 or 2.

4. The composition (M) according to any one of claims 1 to 3, wherein the sum of the component (A) silane crosslink polymer and the component (E) silicone resin is more than 5 wt%, preferably 5 to 15 wt%, more preferably 5 to 10 wt%, based on the total amount of the composition (M) being calculated as 100 wt%.

5. The composition (M) according to any one of claims 1 to 4, wherein the sum of the component (A) silane crosslink polymer, the component (E) silicone resin, the component (B1) epoxy resin and the component (B2) epoxy resin hardener is more than 5 wt%, preferably 5 to 30 wt%, more preferably 5 to 20 wt%, more preferably 10 to 20 wt%, based on the total amount of the composition (M) being calculated as 100 wt%.

6. The composition (M) according to any one of claims 1 to 5, wherein the water content in the composition (M) is 0.1 to 10 parts by weight, more preferably 6 to 10 parts by weight, based on 100 parts by weight of component (A).

7. 1 to 20% by weight of component (A) a silane crosslinked polymer; 1 to 20% by weight of component (B1) an epoxy resin; 0.1 to 1 weight percent of component (B2) an epoxy resin hardener; Optional component (C) an organosilicon compound that does not have a nitrogen atom directly bonded to a carbonyl group; 75 to 85 weight percent of component (D) a thermally conductive filler; 1 to 10% by weight of component (E) silicone resin Contains The composition (M) according to any one of claims 1 to 6, wherein the total amount of all of the compositions (M) is calculated as 100% by weight.

8. the composition is a two-component composition, Component (M1) 3 to 10 weight percent of component (A) a silane crosslinked polymer; 0.1 to 0.5 weight percent of component (B2) an epoxy resin hardener; 0.1 to 1 weight percent of component (C) an organosilicon compound having no nitrogen atom bonded directly to a carbonyl group; 32.5 to 42.5 weight percent of component (D) thermally conductive filler; 3 to 10 weight percent of component (E) a silicone resin; Component (M2) 3 to 10% by weight of component (B1) an epoxy resin; 32.5 to 42.5 weight percent of component (D) thermally conductive filler; 0.1 to 0.5% by weight of water comprising Composition (M) according to any one of claims 1 to 7, wherein the total amount of all of said compositions (M) is calculated as 100% by weight.

9. The composition (M) according to any one of claims 1 to 8, having an initial adhesive strength of 1 Mpa or more at 24 hours and a final adhesive strength of 6 Mpa or more at 14 days after curing at room temperature with a humidity of 50% according to GB / T 7124-2008.

10. A method comprising applying and / or caulking and / or potting a composition (M) according to any one of claims 1 to 9 into gaps between substrates and / or electronic devices prior to crosslinking and / or curing.

Citation Information

Patent Citations

  • Silicone-based adhesive composition

    JP2007191502A